Towards a dignity manifesto of design - for people living with dementia - Fleming, Richard; Zeisel, John; Bennett, Kirsty; Golembiewski, Jan; Swaffer, Kate; Henderson, Lynda (Architectural science review, 2023)
This editorial is intended to introduce The Dignity Manifesto of Design and request meaningful commentary on this guide for environments for people living with dementia, so that design will support values of dignity, autonomy, independence, equality of opportunity, and non-discrimination. The two-part manifesto - a short list of values followed by ten design principles - follows Recommendation 1 of the Alzheimer's Disease International World Alzheimer's Report 2020.